Selecting Career Criminals for Priority Prosecution, 1984-1986: Los Angeles County, California and Middlesex County, Massachusetts - Chaiken, Marcia R. ([Verlag nicht ermittelbar], 1989)
Collection of these data was undertaken in order to develop offender classification criteria that could be used to identify career criminals for priority prosecution. In addition to the crime records obtained from official sources and defendants' self- reports, information about prosecutors' discretionary judgments on sampled cases was obtained from interviews of prosecutors and case review forms completed by attorneys. Respondent and nonrespondent files, taken from official court records, contain information on current and past records of offenses committed, arrests, dispositions, sentences, parole and probation histories, substance abuse records, juvenile court appearances, criminal justice practitioners' assessments, and demographic characteristics. The prosecutor interview files contain variables relating to prosecutors' opinions on the seriousness of the defendant's case, subjective criteria used to decide suitability for prosecution, and case status at intake stage. Information obtained from prosecutors' case review forms include defendants' prior records and situational variables related to the charged offenses. The self-report files contain data on the defendants' employment histories, substance abuse and criminal records, sentence and confinement histories, and basic socioeconomic characteristics.